Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015): III All-Russian Scientific and Practical Conference, 27–31 July 2015, Altai, Russia; [proceedings]; Journal of Physics: Conference Series (2016, 2016)
Title screen